Synthesis of lichen response to gaseous nitrogen: Ammonia versus nitrogen dioxide. (1st January 2023) - Greaver, Tara; McDow, Stephen; Phelan, Jennifer; Kaylor, S. Douglas; Herrick, Jeffrey D.; Jovan, Sarah
Abstract: The dominant chemical form of nitrogen pollution in the atmosphere in the U.S. is shifting from oxidized nitrogen, primarily from combustion of fossil fuels, to reduced nitrogen from agricultural animal waste and fertilizer applications. Does it matter to lichens? In this synthesis, we characterize U.S. air concentrations of the most ubiquitous gaseous forms of reduced and oxidized nitrogen, NO2 and NH3, respectively, and their direct effects on lichens. In the U.S., the 3-year average (2017–2019) of the annual mean for each monitoring site ranges up to 56.4 μg NO2 m −3 (∼30 ppb) and 6 μg NH3 m −3 (∼9 ppb). The spatial coverage of current routine monitoring of NO2 and NH3 likely does not accurately represent exposures of NO2 to ecosystems in rural areas or capture spikes of NH3 concentrations proximal to intensive agriculture, which are documented to exceed 700 μg NH3 m −3 (∼1000 ppb) for short durations. Both NO2 and NH3 can act as nutrients to lichens, but as exposures rise, both can cause physiological stress and mortality that then change community composition and diversity. There is a growing body of evidence that lichen community composition is altered at current levels of exposure in the U.S. with estimated no effect or lowest effect concentrations from <1 to 3 μg m −3 NO2 and <1 μg m −3 NH3 . Better spatial characterization of both NO2 and NH3 concentrations, especially near intensive agriculture, would help to characterize the extent of the impacts across the U.S. These findings are discussed in the context of U.S. air pollution policy. Highlights: Evidence supports that lichen community composition is altered at <1-3 µg NO2 m -3 and <1 µg NH3 m -3 . The 3-year average (2017-2019) for monitoring sites in the U.S. ranges up to 56.4 µg NO2 m -3 and 6 µg NH3 m -3 . Better spatial characterization of NO2 and NH3 concentrations, especially near intensive agriculture, are needed in the U.S.